(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: An understanding of the cardiovascular effects of patients with chronic kidney diseases on maintenance haemodialysis is essential. Objectives: The objectives of the present study were to understand the cardiovascular changes and complications in patients with chronic kidney disease on maintenance haemodialysis. Methods: This was a single centre non-randomized prospective observational study conducted at Department of General Medicine, Government Villupuram Medical College, Villupuram, Tamil Nadu, India between November 2019, and November 2021. The study enrolled hundred adult inpatients admitted with CKD on maintenance haemodialysis consecutively – a non-probability convenient sampling technique. After enrolment, the patients were followed up with ECG, chest X-ray and echocardiography at 3 months and 6 months along with detailed clinical and systemic examination. Results: Of the included 100 patients, two died during the course of the study and none were lost to follow up. The mean (SD) age of the patients was 42.4 (10.1) with male preponderance in all age groups. The male to female ratio was 2.6:1. Pedal oedema and decreased urine output were the commonest symptoms (>90% cases) with a symptom duration ranging between 4 months and 5 years. The present study did not show a statistically significant decline or improvement in haemoglobin during the course of study (p>0.05). The values of blood urea and serum creatinine had a statistically significant reduction at 3 and 6 months compared to baseline (p<0.001). The mean (SD) ejection fraction was 44.3% at the end of 6 months. Majority (83.6%) had systolic dysfunction at 6 months. Left ventricular hypertrophy with echocardiography and cardiomegaly diagnosed with X-ray was found in 53.1% and 35.7% at the end of 6 months. The commonest ECG change noted was LVH (41.8%) followed by sinus tachycardia (19.4%). Conclusion: The findings of the present study will cater to early diagnosis, prompt care and prevention of further complications of cardiovascular effects of patients with chronic kidney diseases on maintenance haemodialysis which will arise during the course of the disease process.